Peningkatan Pemahaman dan Keterampilan Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa Kelas IV SDN Petoran - Wijayanti, Wijayanti; Wianti, Sri; Febriyanti, Karina (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: The practice of Clean and Healthy Lifestyle Behavior (PHBS) among elementary school students still requires attention due to their limited understanding and skills in maintaining personal hygiene, which increases their health risks. Objective: The purpose of this community service was to provide PHBS education to grade IV students at SDN Petoran, Surakarta, using lecture, direct demonstration, and audiovisual media methods. Method: This public service was conducted by engaging 50 students, employing a combination of lectures, direct demonstrations, and audiovisual media to promote PHBS. A pretest and posttest evaluation was conducted to assess the impact of the intervention on the students' understanding and practices. Result: The evaluation results showed a significant improvement in the students' understanding and practices of PHBS, particularly in activities such as handwashing and tooth brushing, which they now perform independently. Paired t-test analysis supported these findings, confirming that the demonstration approach was effective in fostering sustainable healthy habits. Conclusion: This activity is expected to contribute to national efforts to raise health awareness in primary education settings and has the potential to provide long-term health benefits for children.